Sinonim Leksikal Berdasarkan Artikel CNN: Berita Terkini AS & Dunia: BERITA TERKINI AS & DUNIA. - Tampani, Enzigo Divio; Mayasari, Mayasari; Geubrina, Misla (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2025)
This research was intended to describe the types of lexical synonymy in CNN Articles: Breaking US & World News. The study of lexical synonymy is a branch of semantics that focuses on the meaning of words. This research used Alan Cruse’s theory. Lexical synonymy is words with very closely related meanings. There are three types of lexical synonymy namely absolute synonymy, propositional synonymy, and near-synonymy. The design of this research was a qualitative method. The researcher got the source of data from CNN articles. The researcher analyzed lexical synonymy from four articles in CNN. Then, the researcher categorized the types of lexical synonymy. The result of this research shows that in CNN Articles: Breaking US & World News consist of 27 samples of lexical synonymy. The samples are 7 of absolute synonymy, 10 of propositional synonymy, and 10 of near-synonymy.